Telhados verdes extensivos: influência da composição do substrato na retenção hídrica e no desenvolvimento da vegetação - Liberalesso, Tiago (2018)
The increasing of the impermeable surfaces caused by urbanization process, allied with the lack of planning of infrastructures facilities, have contributed to environmental degradation and consequently reducing life quality in urban centers. In this light, green roofs are emerging as good option for reducing these negative impacts by improving stormwater management, reducing the runoff, mitigating the urban heat island effects, increasing urban biodiversity and providing a more aesthetically pleasing and healthy environment. Of all the green roof's system, the growing media (substrate) is the essential part in the design and success of the system. The substrate developed from environmental liabilities provides the improvement of environmental quality as well as lowering production costs, increasing the green roofs sustainability. In that context, some substrate compositions were developed for application on extensive green roofs, using civil construction waste and residues from rice production as raw materials. Crushed bricks (fixed proportion of 20%), rice husk (natural - CAN and carbonized - CAC), soil in different volumetric proportions, vermicompost and vermiculite (fixed proportions of 15% each) were used in these compositions. Physical and chemical properties of each substrate, the runoff water quality and the vegetation development set to the different treatments were evaluated. The composition with higher content of carbonized rice husk showed the most desirable physical attributes, reducing the density of the substrates and, consequently, the load on the building's structure. The treatments SC4 (20% CAC and 30% soil) and SCOM (commercial substrate of peat) showed a better retention capacity, retaining respectively 79.76% and 85.27% of the volume of precipitation, during the monitoring period. Treatments with natural rice husk showed the lowest vegetation cover rate. All substrates affected negatively the water quality, increasing the content of solids and phosphorus. As the main findings of this study, it was concluded therefore that it is very difficult to set a single composition that meets all the ‘desirable’ characteristics of a green roof substrate. Therefore, deeper researches must be carried out to advance in the study of the best composition of substrates for green roofs systems.